2021
DOI: 10.1021/acssuschemeng.1c01450
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Beech Wood into Antiviral Lignin–Carbohydrate Complexes by Microwave Acidolysis

Abstract: Virus pandemics pose a threat to human life. In this study, we developed a simple method for the conversion of woody biomass into antiviral substances. Beech wood was decomposed by microwave acidolysis in 0.5% aq H2SO4 and fractionated by silica gel chromatography. The obtained fractions exhibited strong antiviral activity against encephalomyocarditis virus (EMCV) without cytotoxicity. Structural analyses revealed that the separated antiviral substances were lignin–carbohydrate complexes with molecular weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
(88 reference statements)
0
14
0
Order By: Relevance
“…LCC isolated from beech wood through microwave acidolysis is effective against encephalomyocarditis virus. Decoupling of carbohydrate moieties from these LCC significantly suppresses the antiviral activity, emphasizing the importance of carbohydrate moieties on LCC for biological activities (Li et al, 2021).…”
Section: Lignin-carbohydrate Complexmentioning
confidence: 99%
“…LCC isolated from beech wood through microwave acidolysis is effective against encephalomyocarditis virus. Decoupling of carbohydrate moieties from these LCC significantly suppresses the antiviral activity, emphasizing the importance of carbohydrate moieties on LCC for biological activities (Li et al, 2021).…”
Section: Lignin-carbohydrate Complexmentioning
confidence: 99%
“…A powerful tool for the characterization of functionalized silica is 13 C and 29 Si NMR which permits analysis of the evolution of the chemical environment around silicon atoms introduced by addition of active components. The 29 Si NMR of bare silica presents features to be attributed to silicon without hydroxy groups Si-(O-Si) 4 , silicon atoms bearing one hydroxy group (Si-O) 3 -Si-OH and silicon atoms bearing two hydroxy groups (Si-O) 2 -Si-(OH) 2 called germinal silanols. The first species, whose peak is named Q 4 , is largely present in the bulk whereas the second and the third (respectively called Q 3 and Q 2 ) are present at the silica surface.…”
Section: Sulfonic Acid-functionalized Materials: Characterizationmentioning
confidence: 99%
“…The 29 Si NMR of bare silica presents features to be attributed to silicon without hydroxy groups Si-(O-Si) 4 , silicon atoms bearing one hydroxy group (Si-O) 3 -Si-OH and silicon atoms bearing two hydroxy groups (Si-O) 2 -Si-(OH) 2 called germinal silanols. The first species, whose peak is named Q 4 , is largely present in the bulk whereas the second and the third (respectively called Q 3 and Q 2 ) are present at the silica surface. In addition to the changes in proportion between these peaks, when functionalized, a new set of peaks in the range {−45;−80} ppm appears giving evidence for the covalent incorporation of the functional groups.…”
Section: Sulfonic Acid-functionalized Materials: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that the anti-EMCV lignin− carbohydrate complex was produced from beech wood by microwave acidolysis. 22 We also reported that anti-EMCV lignin was produced via microwave glycerolysis of sugarcane bagasse, an agro-industrial lignocellulosic residue. 23 We separated lignin from sugarcane bagasse through acidic microwave glycerolysis at 140, 160, 180, and 200 °C.…”
Section: Introductionmentioning
confidence: 99%